2018
DOI: 10.1039/c8sm00705e
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics of surface nanodroplets during solvent exchange at varying flow rates

Abstract: Solvent exchange is a simple solution-based process to produce surface nanodroplets over a large area. The final size of the droplets is determined by both the flow and solution conditions for a given substrate. In this work, we investigate the growth dynamics of surface nanodroplets during solvent exchange by using total internal reflection fluorescence microscopy (TIRF). The results show that during the solvent exchange, the formation of surface nanodroplets advanced on the surface in the direction of the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…This increase in contact angle (CA) during growth is contrary to the typical formation of water and other organic oils where the surface droplet growth process on a homogeneous substrate is always at a constant contact angle. [35,36] However, this dynamic CA process is consistent with the dewetting process observed with amphiphiles, and shares an interesting parallel with previous simulations which revealed that ionic liquid droplets increased in contact angle as the droplet increased in size. [28] The droplet dewetting phenomenon observed in the whole droplet growth process of about 60 s resembles the autophobing observed for droplets of amphiphile solutions on a substrate, where structuring of the amphiphile at the substrate induces a spontaneous dewetting.…”
Section: Dewetting Phenomenon During Nanodroplet Growthsupporting
confidence: 89%
See 3 more Smart Citations
“…This increase in contact angle (CA) during growth is contrary to the typical formation of water and other organic oils where the surface droplet growth process on a homogeneous substrate is always at a constant contact angle. [35,36] However, this dynamic CA process is consistent with the dewetting process observed with amphiphiles, and shares an interesting parallel with previous simulations which revealed that ionic liquid droplets increased in contact angle as the droplet increased in size. [28] The droplet dewetting phenomenon observed in the whole droplet growth process of about 60 s resembles the autophobing observed for droplets of amphiphile solutions on a substrate, where structuring of the amphiphile at the substrate induces a spontaneous dewetting.…”
Section: Dewetting Phenomenon During Nanodroplet Growthsupporting
confidence: 89%
“…On the other hand, the mean diameter dramatically increased to the maximum value of ≈3 µm in ≈10 s and then gradually reduced and stabilized at ≈2.6 µm at 100 s. The surface coverage illustrated a similar trend: increasing to 38% in the first 10 s and decreasing back to 23% at the end. The reduction in surface coverage was more pronounced than expected for a continual nucleation and growth, which is limited by the competition and continual coalescence between droplets . To further examine the dynamic growth process of an individual droplet, which is identified by a yellow arrow in Figure , has been tracked.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…For the formation of surface nanodroplets, recent work has shown that the flow rate of the solvent exchange is one of the most important parameters that influences the growth dynamics of the droplets [34]. Both theoretical analysis and experimental measurements by total internal reflection microscope confirm that the growth time scales with the square root of the Peclect number (the dimensionless flow rate) of the displacing solvent [35]. The flow rate therefore has significant influence on the size and number density of the droplets.…”
Section: Introductionmentioning
confidence: 96%